Variantion in Ukrainian art terminology - Ovseichyk, Stanislava (Current issues of Ukrainian linguistics: theory and practice, 2018)
The article deals with the variant terms in normative aspect codified in Ukrainian art lexicography of the 21st century. Dictionary codification of variant terms indicates changing in the language and deliberate influence of the society on the development of terminological norm. Variation is a existence form of objects of the surrounding reality, in particular, of scientific concepts, which defines the laws of their function and interaction. The choice of sources is due to the fact that the selected dictionaries are represented modern art knowledge. Dictionaries play a significant role in the normalization of language, the spread of linguistic norms, and therefore they are a grateful and relevant material for the analysis of variation in the Ukrainian art terminology. The article focuses on the importance of the scientific philological study of art terminology – the field of knowledge, which is rapidly developing in modern conditions, acquiring new meanings and forms. The variant terms of the art terminology, codified in Ukrainian special vocabulary, are analyzed. Three types of variant terms, phonemic, derivational and morphological-phonemic units, are fixed in the Ukrainian art terminology. It was found out that among the reasons for the occurrence of phonemic variant terms of the analyzed terminology tends to facilitate articulation of the learned term; the appearance of derivation of variant terms is conditioned by the presence of various derivative models in the Ukrainian language and the search for forms of terms that correspond most closely to modern productive models of term derivation; functioning of morphological-phonemic variant terms is explained by different degrees of grammatical adaptation of foreign-language art terms. It also traces the effect of an analogy inherent to all three of the varieties mentioned. In general, the article discusses the essence of the problem of terminological variation as one of the most relevant processes in the regulation and standardization of the Ukrainian art terminology.